Comparison of spasmolytic regimen for prevention of radial artery spasm during the distal radial approach: A single-center, randomized study - Lee, Oh-Hyun; Roh, Ji Woong; Kim, Yongcheol; Son, Nak-Hoon; Cho, Jay Yi; Jang, Daesek; Im, Eui; Cho, Deok-Kyu; Choi, Donghoon (Frontiers in Cardiovascular Medicine, 2023)
Background: The DRA for coronary catheterization is increasingly being used worldwide yet the optimal medication regimen to prevent RAS, an important factor for the success of the procedure, remains unclear. The aim of this study is to examine the effectiveness of medication for preventing radial artery spasm (RAS) via the distal radial artery approach (DRA). Methods: This was a prospective, comparative randomized study including 400 patients who underwent coronary catheterization via DRA in single center by three experienced DRA operators. Patients were randomized to either nitroglycerin (NTG) injection (N=200) or NTG plus verapamil (N=200) to compare the effectiveness and safety of these regimens. Results: There were no differences between the groups in the changes in radial artery diameter at most spastic area (0.34 ± 0.20 in the NTG group, 0.35 ± 0.20 in the NTG plus verapamil group; P=0.73). There was no difference between the groups in the ratio of patients without arm pain during the procedure (95.0% in the NTG group, 93.5% in the NTG plus verapamil group; P=0.67). However, there was a greater reduction in diastolic blood pressure in the NTG plus verapamil group (-8.3 ±7.9 mmHg) than in the NTG group (-6.6 ± 7.6 mmHg) (P=0.03). Conclusion: Intra-arterial injection of NTG as a single agent is effective and safe in the prevention of RAS during coronary catheterization via the DRA compared with a cocktail regimen of NTG plus verapamil.